Assessment of reference intervals of acylcarnitines in newborns in Siberia - N. V. Nemchinova; T. A. Bairova; A. V. Belskikh; O. V. Bugun; L. V. Rychkova (Acta Biomedica Scientifica, 2022)
Background. The incidence of diseases associated with impaired transport and oxidation of fatty acids is from 1:5,000 to 1:9,000 newborns. High morbidity, risk of death in the absence of timely correction, non-specificity of clinical manifestations define the importance of their timely laboratory diagnosis based on the determination of free carnitine and acylcarnitines in the blood. Reference values for free carnitine and acylcarnitines vary in different populations.   The aim. To determine the reference intervals of free carnitine and acylcarnitines in newborns of the Irkutsk region and to compare them with similar reference intervals in newborns in other countries.   Methods. The analysis of 229 samples of drу blood spots of healthy newborn children of the Irkutsk region aged from 0 to 7 days was carried out. Analysis of acylcarnitine concentrations was performed using high performance liquid chromatography with tandem mass spectrometry.   Results. 2.5 and 97.5 percentiles (µmol/l) were calculateed for 13 acylcarnitines: C0 – [8.78; 38.08]; C2 – [3.55; 19.09]; C3 – [0.33; 1.96]; C4 – [0.08; 0.51]; C5 – [0.06; 0.44]; C5DC – [0.03; 0.17]; C6 – [0.01; 0.07]; C8 – [0.01; 0.07]; C10 – [0.02; 0.07]; C12 – [0.04; 0.51]; C14 – [0.07; 0.24]; C16 – [0.58; 3.25]; C18 – [0.35; 1.16].   Conclusion. Differences in acylcarnitine reference intervals were found: compared with other countries, the concentrations of reference intervals for C0, C2, C3, C5DC, C8, C10, C14, C16 and C18 were lower in our study, reference intervals for C5 and C12 were higher in our country.